The Influence of Mindful Self-compassion Practice for Well-being Among Employees to Enhance Level of Resilience - Vincent Kim Seng OH; Abdullah Sarwar; Niaz PERVEZ (Communications of International Proceedings, 2022)
Workplace challenges faced by Generation Y employees are inevitable. The workplace challenges that arise due to influences of personal issues, social traumas, and outcomes due to the pandemics are some examples of many. Mental suffering can begin outside the workplace, spread to the workplace, and affect the work environment. Self-compassion is kindness shown to oneself during inadequacies, failure, or despair. It can boost job happiness, productivity, and resilience. Studies on the benefits of self-compassion for employees are rising. Resilience is adapting successfully to risk or difficulties. The connection between self-compassion and resilience has been one of the most exciting discoveries in the field of resilience research. With that in mind, the purpose of this conceptual paper is to explore the influence of mindful self-compassion on enhancing the level of resilience among Generation Y to face challenges in their workplace. This paper also discusses the positive relationship between mindfulness, psychological well-being, and the impact on resilience. This paper can guide scholars to begin empirical research on enhancing resilience and deeply investigate mindful self-compassion practice and its effect.
Keywords: Self-compassion; Generation Y; Resilience; Workplace; Psychological Well-Being.